Ar konfucianizmas turi įtakos įmonių socialinės atsakomybės atsiejimui? Įrodymai iš Kinijos - Jinyu, Chen; Zekun, Chen; Juan, Zhang (Transformations In Business & Economics, 2024)
Given the persistent challenge of corporate social responsibility decoupling (CSR decoupling), we conduct a systematic analysis of the impact of Confucianism on CSR decoupling through the lens of informal institutions instead of previous inherent formal institutions. The empirical results show that Confucianism significantly inhibits CSR decoupling. The substitution effect test indicates that this relationship is more evident in companies with poor internal control quality and regions with weak legal environments, suggesting a substitution effect between informal and formal institutions in restraining CSR decoupling. The mechanism test demonstrates that Confucianism primarily restrains CSR decoupling by mitigating managerial myopia and decreasing equity concentration. The heterogeneity analysis suggests that the inhibitory effect of Confucianism on CSR decoupling is more evident in regions experiencing mild cultural conflicts, companies with poorer operating conditions, and state-owned enterprises. Our research contributes to the literature on the relationship between Confucianism and CSR decoupling, offering a novel perspective for addressing this phenomenon.
Keywords: konfucianizmas; ĮSA atsiejimas; teisinė aplinka; vidaus kontrolės kokybė; vadybinė trumparegystė; nuosavo kapitalo koncentracija